2021
DOI: 10.1186/s12967-021-02933-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute intermittent hypoxia on postprandial triglyceride levels in humans: a randomized crossover trial

Abstract: Background Obstructive sleep apnea (OSA), a sleep disorder frequently observed in individuals living with obesity, consists of repeated involuntary breathing obstructions during sleep, leading to intermittent hypoxia (IH). In humans, acute continuous hypoxia slightly increases plasma triglycerides (TG). However, no study yet compared the postprandial TG response of individuals with or without OSA under intermittent hypoxia. Methods Using a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…CPAP withdrawal increased nocturnal NEFA but not TG levels. In line with this observation, Morin et al (2021) recently showed no difference in postprandial TG in individuals with OSA exposed to 6 h of IH or ambient air, in a crossover design.…”
Section: Experimental Evidence Linking Hypoxia and Circulating Triglyceride Levelssupporting
confidence: 54%
See 3 more Smart Citations
“…CPAP withdrawal increased nocturnal NEFA but not TG levels. In line with this observation, Morin et al (2021) recently showed no difference in postprandial TG in individuals with OSA exposed to 6 h of IH or ambient air, in a crossover design.…”
Section: Experimental Evidence Linking Hypoxia and Circulating Triglyceride Levelssupporting
confidence: 54%
“…Recent evidence also suggests that the gastrointestinal tract seems to cope well with hypoxia exposure. More precisely, no difference was observed in the circulating CM-TG of healthy individuals after 6 h of normobaric hypoxia (FiO 2 = 100%) after a meal ( Morin et al, 2021 ).…”
Section: Underlying Mechanisms By Which Hypoxia Modulates Triglycerides Levelsmentioning
confidence: 94%
See 2 more Smart Citations
“…Under hypoxic conditions, oxygen availability becomes limited and oxidative phosphorylation is hampered ( Solaini et al, 2010 ). Experiments in humans studying the metabolic responses to hypoxia in continuous and intermittent forms, and under fed or fasted state, showed that hypoxia significantly increases plasma NEFA concentrations ( Jun et al, 2011 ; Mahat et al, 2016 , 2018 ; Chopra et al, 2017 ; Mauger et al, 2019 ; Morin et al, 2021 ), which should translate into an increased ketogenesis. In this regard, limited studies conducted in rodents have reported that circulating ßOHB levels significantly increase in response to acute hypoxic exposure ( D’Alecy et al, 1990 ; Jun et al, 2012 ; Rising and D’Alecy, 1989 ).…”
Section: Introductionmentioning
confidence: 99%